ISLAMIC EDUCATION IN FACING THE PHENOMENA OF GLOBALIZATION: - SURADI, AHMAD (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract In general, the epistemology of Islamic educational science has three strong tendencies, namely epistemology serve is epistemology which assumes that the source of knowledge is the revelation (text) or reasoning of the text. Irfani epistemology is epistemology which assumes that science is the will (irodah). Burhani epistemology is an epistemology which holds that the source of science is reason. Reason according to this epistemology has the ability to find a variety of knowledge, even in the midwife of religion even though the intellect is able to know it, such as good and bad problems (tansin and tahbih). With this, it is theologically justified from the Qur'an. In the Qur'an many verses are found which speak of knowledge derived from rationality. With that, Islamic education should change the format, form, orientation and educational method with the record not to change the vision, mission and orientation of Islamic teachings themselves, but the changes are only on the outside only, while on the inside is still maintained. In many ways, Islamic education systems and institutions have been modernized and adapted to the demands of development and, with the goal of contemporary Islamic education, not only changed the sociocultural and educational base of the students alone but also the Islamic education is expected to solve the moral and ethical problems of science modern. Keywords: Epistemology, Islamic Educational Philosophy, Globalization